One Hundred Pressing Questions on the Future of Global Fish Migration Science, Conservation, and Policy - Lennox, Robert J.; Paukert, Craig P.; Aarestrup, Kim; Auger-Méthé, Marie; Baumgartner, Lee; Birnie-Gauvin, Kim; Bøe, Kristin; Brink, Kerry; Brownscombe, Jacob W.; Chen, Yushun; Davidsen, Jan G.; Eliason, Erika J.; et al. (Frontiers in Ecology and Evolution, 2019)
Migration is a widespread but highly diverse component of many animal life histories. Fish migrate throughout the world’s oceans, within lakes and rivers, and between the two realms, transporting matter, energy, and other species (e.g. microbes) across boundaries. Migration is therefore a process responsible for myriad ecosystem services. Many human populations depend on the presence of predictable migrations of fish for their subsistence and livelihoods. Although much research has focused on fish migration, many questions remain in our rapidly changing world. We assembled a diverse team of fundamental and applied scientists who study fish migrations in marine and freshwater environments to identify pressing unanswered questions. Our exercise revealed questions within themes related to understanding the migrating individual’s internal state, navigational mechanisms, locomotor capabilities, external drivers of migration, the threats confronting migratory fish including climate change, and the role of migration. In addition, we identified key requirements for aquatic animal management, restoration, policy, and governance. Lessons revealed included the difficulties in generalizing among species and populations, and in understanding the levels of connectivity facilitated by migrating fishes. We conclude by identifying priority research needed for assuring a sustainable future for migratory fishes.